Consumption of ultra-processed foods and associated factors in children from Barbacena (MG), Brazil - Marlene de Melo Fonseca; Rafaela Vitoria Guilherme Coimbra; Julia Silva e Oliveira; Anne Danieli Nascimento Soares; Júnia Maria Geraldo Gomes (Sociedade de Pediatria de São Paulo, 2023)
Abstract Objective: To evaluate the prevalence of ultra-processed food consumption and associated factors among children enrolled in the public school system of the city of Barbacena, Minas Gerais, Brazil. Methods: This is a cross-sectional study conducted with schoolchildren aged 7-9 years, of both sexes, enrolled in state public schools. Food intake was assessed using the Previous Day Food Questionnaire and the level of physical activity by the Previous Day Physical Activity Questionnaire. The listed foods were classified according to the extent and purpose of industrial processing, using the NOVA classification. Pearson's χ2 test, Fisher's exact test, χ2 with Yates correction, and Poisson regression were used in the statistical analysis, estimating the crude and adjusted prevalence ratio, with 95% confidence intervals. Results: The prevalence of daily ultra-processed food consumption was 69.6%. After adjusted analyses, the consumption of ultra-processed food was associated with the omission of breakfast, mid-afternoon snack, supper, low physical activity, and consumption of risk foods. On the other hand, consumption of in natura or minimally processed foods was associated with older age, the consumption of lunch, mid-afternoon snack, dinner, and protective foods. Conclusions: There is a high prevalence of ultra-processed foods consumption, associated with unhealthy dietary habits among schoolchildren. This highlights the need for nutritional counseling and educational actions, favoring healthy eating in childhood.